2017
DOI: 10.1101/185074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha oscillations control cortical gain by modulating excitatory-inhibitory background activity

Abstract: SUMMARYThe first recordings of human brain activity in 1929 revealed a striking 8-12 Hz oscillation in the visual cortex. During the intervening 90 years, these alpha oscillations have been linked to numerous physiological and cognitive processes. However, because of the vast and seemingly contradictory cognitive and physiological processes to which it has been related, the physiological function of alpha remains unclear. We identify a novel neural circuit mechanism-the modulation of both excitatory and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 113 publications
(227 reference statements)
6
31
0
Order By: Relevance
“…Overall, our results suggest that stimulus-related responses are boosted during a liberal criterion due to increased cortical response gain, which is further supported by recent work linking alpha power suppression to enhanced gain 42 .…”
Section: Discussionsupporting
confidence: 75%
“…Overall, our results suggest that stimulus-related responses are boosted during a liberal criterion due to increased cortical response gain, which is further supported by recent work linking alpha power suppression to enhanced gain 42 .…”
Section: Discussionsupporting
confidence: 75%
“…In line with these 1217 observations, Peterson & Voytek (2017) recently proposed alpha 'bursts' to increase visual gain 1218 during stimulus onsets and contrasted this role with decreased cortical processing during 1219 sustained alpha rhythms. Our data supports such a distinction between sustained and transient 1220 events, although it should be noted that the present transients resemble single time-domain 1221 deflections that are resolved at alpha frequency ( Figure 10A2) and may therefore not directly 1222 relate to the 'rhythmic bursts' proposed by Peterson & Voytek (2017). Note that the reported 1223 duration of 'burst' events in the literature is still diverse, often exceeding the 3-cycle threshold 1224 used here (Peterson & Voytek, 2017).…”
supporting
confidence: 57%
“…Our data supports such a distinction between sustained and transient 1220 events, although it should be noted that the present transients resemble single time-domain 1221 deflections that are resolved at alpha frequency ( Figure 10A2) and may therefore not directly 1222 relate to the 'rhythmic bursts' proposed by Peterson & Voytek (2017). Note that the reported 1223 duration of 'burst' events in the literature is still diverse, often exceeding the 3-cycle threshold 1224 used here (Peterson & Voytek, 2017). In contrast to eBOSC however, previous work has not 1225 accounted for the impact of wavelet duration.…”
supporting
confidence: 57%
“…A well-described mechanism of attentional stimulus selection is gain regulation of population responses in sensory regions 2,3 . MEG and EEG studies have shown that gain regulation can be reflected in alpha band dynamics 4 . This has been demonstrated in several studies with respect to anticipatory biasing of visual processing in visuospatial cueing [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%